Surgical Management of Exuberant Granulation Tissue in Equines: A Study of Eight Cases - Saharan, Sandeep; Singh, Prem; Gupta, R. P.; Singh, Ajit; Dutt, Ravi (International Journal of Livestock Research, 2023)
Exuberant granulation tissue, commonly known as proud flesh/ fibroplasia, is a frustrating complication of wound healing and is mostly seen in the equines. The study was conducted on eight (six males and two females) clinical cases of exuberant granulation tissue (EGT) in equines brought to Veterinary Clinical Complex (VCC). Lesions were 15 days to 6 months old in these cases. Being more prone to injury, the limbs were affected in five cases. Surgical resection of this EGT was carried out in all the cases and the biopsy samples were taken. Histopathologically, granulation tissue was characterized by the proliferation of fibrous tissue along with blood vessels and inflammatory cells. Homecare was done with the help of antibiotics, analgesics, Vitamin-B Complex, and Vit. C. All the cases recovered after 2-3 weeks of the treatment without any complications.